If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 5 + -2y = 5y + 3 + 2x Reorder the terms: 5 + y + -2y = 5y + 3 + 2x Combine like terms: y + -2y = -1y 5 + -1y = 5y + 3 + 2x Reorder the terms: 5 + -1y = 3 + 2x + 5y Solving 5 + -1y = 3 + 2x + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 5 + -1y + -5y = 3 + 2x + 5y + -5y Combine like terms: -1y + -5y = -6y 5 + -6y = 3 + 2x + 5y + -5y Combine like terms: 5y + -5y = 0 5 + -6y = 3 + 2x + 0 5 + -6y = 3 + 2x Add '-5' to each side of the equation. 5 + -5 + -6y = 3 + -5 + 2x Combine like terms: 5 + -5 = 0 0 + -6y = 3 + -5 + 2x -6y = 3 + -5 + 2x Combine like terms: 3 + -5 = -2 -6y = -2 + 2x Divide each side by '-6'. y = 0.3333333333 + -0.3333333333x Simplifying y = 0.3333333333 + -0.3333333333x
| 5x+6=3x+9 | | 28-4x=7-7x | | 10x-16=9x+2 | | 5(x+4)=3x+29 | | 4(x+2)-2=18 | | y-3.5=-21 | | -5j+78=8j-2 | | 3x-19=5x+2 | | 5-(2u-1)=14-4u | | x*2-2x=0 | | 3x-19=x-2 | | 2.23-3.14x=2x-4.195 | | 2(4x+3)=2 | | 4x-15=x+10 | | 5x-12=2x-9 | | 2H+4S=22 | | 5(x-3)=-13 | | 19-x+4+x+19+x-1=34 | | 3x=1.08 | | F(x)=(radx-2)-3 | | ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 | | 0.04*0.8= | | x+(2x+15)=150 | | 0.75d-0.67d=0.67+6 | | 88+5x= | | K-(-6)=-33 |